A New Progressive and Efficient Royalty Model for Upstream Petroleum Industry - Mohamed, Ibrahim S.; Khttab, Hamid M.; Elsayed, Said K.; El-Noby, Mohsen G.; Elrammah, Shady G. (International Journal of Energy Economics and Policy, 2022)
In this research paper, a new methodology to design a progressive and win-win royalty model for upstream fiscal systems is developed. The proposed royalty model is designed as a function of different boundary conditions of the market and the productive resources. These boundary conditions include the associated exploration and production risks, commodity prices, the extraction costs, besides the expected production and depletion rate. The behavior of the proposed royalty model under different oil prices, development costs, production rates, and exploration risks is investigated using deterministic and stochastic analysis. Our results prove that the applicable royalty rate increases with both the price and production rate while it decreases with increasing the development costs and the associated exploration and production risks. In addition, the proposed royalty model provides the contractor with sufficient incentives to develop marginal or low profitability fields and the development of deep offshore or frontier fields with high development and operating costs.